PENGARUH ANGGARAN PERTAHANAN DAN MINIMUM ESSENTIAL FORCE DALAM MENGHADAPI ANCAMAN NON MILITER: (Studi di Direktorat Jenderal Kekuatan Pertahanan) - Mulyani; Muhtar Rifai; Ansar Tutu; Andi Sunra; Kasih Prihantoro (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Abstract: National defense is a government function that is carried out through a universal defense system. Defense is functioned to deal with urgent threats to national security and defense not only limited to space and time, but also to the strategic environment at the global, regional, and national levels. The conditions faced by the COVID-19 pandemic have weakened several sectors. Through the program of military operations other than war (OMSP), the Indonesian National Armed Forces together with related institutions are trying to strengthen each other in actions to stabilize the country. For this reason, it is very important to prepare the defense budget in optimizing personnel and material capabilities. This research is focused on knowing the effect of the defense budget and minimum essential force in facing non-military threats partially or simultaneously. This research method uses a survey with data collection through questionnaires. This research is associative quantitative research which aims to find the influence or relationship between variables. The sample used is 76 respondents. Data processing using SPSS 21.0 analysis for the data quality test process, classical assumption test, and multiple linear regression test. The results achieved in this study include, (1) the defense budget and the minimum essential force simultaneously have a positive and significant effect in dealing with non-military threats, (2) the budget has a positive and significant effect in dealing with non-military threats, (3) the minimum essential force has an effect on positive and significant in dealing with non-military threats.